Exercise promotes peripheral glycolysis in skeletal muscle through miR-204 induction via the HIF-1α pathway - Sang R. Lee; Kang Joo Jeong; Moeka Mukae; Jinhee Lee; Eui-Ju Hong (Scientific Reports)
Abstract The mechanisms underlying exercise-induced insulin sensitization are of great interest, as exercise is a clinically critical intervention for diabetic patients. Some microRNAs (miRs) are secreted from skeletal muscle after exercise where they regulate insulin sensitivity, and have potential as diagnostic markers in diabetic patients. miR-204 is well-known for its involvement in development, cancer, and metabolism; however, its role in exercise-induced glycemic control remains unclear. In the present study, endurance exercise in mice increased miR-204 expression levels in skeletal muscle. In a chronic exercise model, miR-204 expression levels were elevated along with glycolytic enzymes in skeletal muscle. When muscular hypoxia was induced after exercise, miR-204 expression also increased with the upregulation of hypoxia-inducible factor 1-alpha (HIF-1α). Furthermore, HIF-1α overexpression led to increased miR-204 expression. Treatment with a miR-204 mimic in C2C12 cells significantly enhanced the glycolysis rate and the mRNA expression of glycolytic enzymes. Notably, intravenous administration of miR-204 in mice increased the glucose clearance rate following refeeding. miR-204 initially elevated blood glucose levels at an early stage of refeeding but later promoted blood glucose reduction as refeeding continued. Additionally, glycolytic enzymes were upregulated in the skeletal muscles of miR-204-injected mice. These findings suggest a novel physiological role for miR-204 in promoting skeletal muscle glycolysis, particularly in situations where insulin action is limited.